Self-powered photoelectrochemical sensor for chlorpyrifos detection in fruit and vegetables based on metal–ligand charge transfer effect by Ti3C2 based Schottky junction. (15th August 2022) - Du, Xiaojiao; Du, Wenhan; Sun, Jun; Jiang, Ding
Highlights: A novel self-powered PEC sensor was developed for CPF assay. The Schottky junction was made for enhanced photoelectric conversion efficiency. MLCT effect induced the excellent selectivity of the sensor. The sensor can be used to determine CPF in apple and cucumber samples. Abstract: Herein, a high-performance self-powered photoelectrochemical (PEC) sensor was fabricated for chlorpyrifos (CPF) assay based on the noble-metal-free AgBr/Ti3 C2 Schottky interface in fruit and vegetables. The Schottky barrier could provide an electron-transfer irreversible passage from AgBr to Ti3 C2 nanosheets, and thus improving the light absorption and efficiency of charge separation. Such Schottky interface exhibited an ultrasensitive and selective photocurrent response for CPF due to the metal–ligand charge transfer effect. Because Ti3 C2 MXene nanosheet had coordinative interaction with CPF and thus suppressed its photocurrent response of the Schottky interface, which was further confirmed by the electrochemical impedance spectra and X-ray photoelectron spectroscopy. The developed self-powered PEC sensor showed wide linear range (1 × 10 −3 ∼ 1 ng L −1 ), low detection limit (0.33 pg L −1 ), limit of quantitation (1 pg L −1 ), good reproducibility and stability. The sensor was applied for the determination of CPF in river water, apple and cucumber samples with good satisfactory results.